2015
DOI: 10.1515/zpch-2015-0637
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction Kinetics of Amino Radicals with Sulfur Dioxide

Abstract: Application of the laser photolysis-laser-induced fluorescence method to the reaction NH 2 + SO 2 in argon bath gas yields pressure-dependent, thirdorder kinetics which may be summarized as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Consequently, a subset for NH 2 SO 2 was established and implemented in the model. The NH 2 SO 2 adduct is formed by recombination of NH 2 and SO 2 The kinetic data for this reaction were adopted from the study of Gao et al There is no information reported about consumption reactions for NH 2 SO 2 , so a subset was established with estimated rates (see SI). However, based on the thermodynamic properties of NH 2 SO 2 , calculated in the present work, the thermal stability of this species is too low for it to be important at temperatures relevant for SNCR.…”
Section: Modeling Approachmentioning
confidence: 99%
“…Consequently, a subset for NH 2 SO 2 was established and implemented in the model. The NH 2 SO 2 adduct is formed by recombination of NH 2 and SO 2 The kinetic data for this reaction were adopted from the study of Gao et al There is no information reported about consumption reactions for NH 2 SO 2 , so a subset was established with estimated rates (see SI). However, based on the thermodynamic properties of NH 2 SO 2 , calculated in the present work, the thermal stability of this species is too low for it to be important at temperatures relevant for SNCR.…”
Section: Modeling Approachmentioning
confidence: 99%
“…The present study shows that the branched isomer, HNSO 2 , which is isoelectronic with SO 3 is 18.3 kcal/mol more stable than the unbranched HONSO. The thermochemical calculations by Gao et al showed that HNSO 2 is having SN bond dissociation enthalpy of 33.8 kcal/mol more than the atmospherically relevant radical H 2 NSO 2 . The theoretical calculations by Williams et al reported that HNSO 2 is an isolable species and is about 4.5 kcal/mol more stable than its SO 3 analogue .…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] However, the interaction between nitrogen and sulfur chemistry in combustion is still a field with major uncertainty. [33] After studying the literature studies [11,14,16,20,21,30] about the reaction mechanism between nitrogen and sulfur species, this article systematically summarizes and selects 12 reactions (R1-R12) of small sulfur-containing molecules with NO and NO 2 . These reactions and the roles and significance of these reactions are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%